Improve Long-Term Biodiversity Management and Monitoring on Certified Oil Palm Plantations in Colombia by Centralizing Efforts at the Sector Level - Furumo, Paul R.; Barrera-Gonzalez, Edgar I.; Espinosa, Juan C.; Gómez-Zuluaga, Gustavo A.; Aide, T. Mitchell (Frontiers in Forests and Global Change, 2019)
Commodity crop expansion remains a leading driver of deforestation and defaunation in the tropics. Voluntary certification standards are the primary mechanism for making commodity production more sustainable and rely on the High Conservation Value (HCV) framework for protecting biodiversity on farms. In the oil palm sector, the HCV approach requires producers to create a management and monitoring plan for on-farm species and habitat, but many companies struggle with interpreting and implementing recommendations from HCV reports. In this study, we explore the challenges to effective biodiversity monitoring on oil palm plantations by consulting recommendations from twenty-one HCV reports for RSPO-certified projects in Latin America, and conducting semi-structured interviews with eight RSPO-certified palm oil mills in Colombia to understand how companies adopt recommendations. We identified several shortcomings under the HCV management-monitoring process including lack of indicators and guidance in HCV reports, emphasis on operational (i.e. procedural) over strategic (i.e. effectiveness) monitoring, over-reliance on incidental wildlife encounters for monitoring populations, and significant technical and financial barriers facing companies. We provide recommendations for improving these aspects including the adoption of Essential Biodiversity Variables (EBV)—population state variables that bridge raw data with global indicators for policymakers—to guide and standardize monitoring on plantations. We conclude by proposing a strategy for biodiversity monitoring that is long-term, driven by EBVs, and centralized at the sector level in Colombia to improve standardization and reduce costs. Current company efforts track drivers of biodiversity trends that complement EBVs, and should continue to encourage staff buy-in and awareness of biodiversity conservation importance.